REAKSI PASAR MODAL INDONESIA TERHADAP PERISTIWA POLITIK INTERNASIONAL (Studi Tentang Pemilihan Presiden Amerika Serikat Tahun 2020) - Jidan Apriyanto (2021)
The purpose of this study is to determine the reaction of the Indonesian capital market when international political events occur. This research was conducted on companies that were included in LQ45 for the period August 2020 - January 2021, using the saturated sample method. With the single index model technique to find the abnormal return. And the event window period is 15 days, and the estimation period is 30 days with a combined data analysis technique between One Sample t-test, one sample Wilcoxon signed rank test and Paired sample t-test. The results of the analysis show that there are no significant abnormal returns around the event period, but there are differences in abnormal returns between before and after the announcement of the results of the 2020 United States presidential election. Meanwhile, there is significant trading volume activity for 15 days around the event period. There was a reaction in LQ45 on abnormal returns but not significant with significant trading volume activity.